2011
DOI: 10.1016/j.neuron.2011.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Rare De Novo and Transmitted Copy-Number Variation in Autistic Spectrum Disorders

Abstract: To explore the genetic contribution to autistic spectrum disorders (ASDs), we have studied genomic copy-number variation in a large cohort of families with a single affected child and at least one unaffected sibling. We confirm a major contribution from de novo deletions and duplications but also find evidence of a role for inherited "ultrarare" duplications. Our results show that, relative to males, females have greater resistance to autism from genetic causes, which raises the question of the fate of female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
551
7
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 671 publications
(601 citation statements)
references
References 46 publications
34
551
7
9
Order By: Relevance
“…Thanks to the comparative genomic hybridization (CGH) technique or SNPs array, CNVs were also found in multiple chromosomal regions at 1q21.1, 16p11.2, 17q12, and 22q11.2 (Jacquemont et al., 2006; Marshall et al., 2008; Matsunami et al., 2013; O'Roak et al., 2012; Pinto et al., 2010; Sebat et al., 2007). Further studies supported the association with ASD of two recurrent de novo CNVs at 16p11.2 (duplication and deletion) and 7q11.23 (duplication; Levy et al., 2011; Sanders Stephan et al., 2011). The chromosomal deletion found at 7q11.23 has been linked to William's syndrome, which includes intellectual disabilities, facial dysmorphic features, congenital heart defect, and transient hypercalcemia.…”
Section: Reviewmentioning
confidence: 99%
“…Thanks to the comparative genomic hybridization (CGH) technique or SNPs array, CNVs were also found in multiple chromosomal regions at 1q21.1, 16p11.2, 17q12, and 22q11.2 (Jacquemont et al., 2006; Marshall et al., 2008; Matsunami et al., 2013; O'Roak et al., 2012; Pinto et al., 2010; Sebat et al., 2007). Further studies supported the association with ASD of two recurrent de novo CNVs at 16p11.2 (duplication and deletion) and 7q11.23 (duplication; Levy et al., 2011; Sanders Stephan et al., 2011). The chromosomal deletion found at 7q11.23 has been linked to William's syndrome, which includes intellectual disabilities, facial dysmorphic features, congenital heart defect, and transient hypercalcemia.…”
Section: Reviewmentioning
confidence: 99%
“…Over the past several years, genome-wide association studies (GWAS) have revealed a handful of common alleles of modest effect size likely to contribute to ASD [46-48]. Analysis of CNV has additionally implicated rare genomic structural changes, both de novo and inherited, of large effect size [20,21,49-52]. Most recently, exome sequencing has lent insight into the contribution of de novo SNVs [22-25].…”
Section: The Current State Of Autism Geneticsmentioning
confidence: 99%
“…For simplicity, these models are presented as distinct categories, whereas in reality ASD risk is likely to be represented by a more continuous distribution of risk architecture. A single asterisk indicates that there is evidence to suggest that de novo CNVs in unaffected controls are smaller [21,51,52] and less gene-rich [20,21] than in people with ASD. A double asterisk indicates that there is conflicting evidence for increased oligogenic heterozygosity [25,156].…”
Section: The Current State Of Autism Geneticsmentioning
confidence: 99%
See 2 more Smart Citations